2023
DOI: 10.1002/ptr.7902
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic prospects of naturally occurring p38 MAPK inhibitors tanshinone IIA and pinocembrin for the treatment of SARS‐CoV‐2‐induced CNS complications

Abstract: P38 mitogen‐activated protein kinase (p38 MAPK) signaling pathway is closely related to severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) replication and hyperinflammatory responses in coronavirus disease 2019 (COVID‐19). Therefore, blood–brain barrier‐penetrating p38 MAPK inhibitors have good potential for the treatment of central nervous system (CNS) complications of COVID‐19. The aim of the present study is the characterization of the therapeutic potential of tanshinone IIA and pinocembrin for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 145 publications
(184 reference statements)
0
5
0
Order By: Relevance
“…Recent studies have shown that Tanshinone IIA (Figure 8) inhibits P38 mitogen-activated protein kinase (p38 MAPK) linked to both the replication and inflammatory effects of COVID-19. Interestingly, these inhibitors can penetrate the blood-brain barrier, making their potential application possible in the treatment of central nervous system complications induced by COVID-19 (Valipour, 2023). The demonstrated biological properties of Tanshinone IIA also make it potentially useful in the treatment of various pathologies (Shang et al, 2012).…”
Section: S Miltiorrhiza Bunge (Dan Shen)mentioning
confidence: 99%
“…Recent studies have shown that Tanshinone IIA (Figure 8) inhibits P38 mitogen-activated protein kinase (p38 MAPK) linked to both the replication and inflammatory effects of COVID-19. Interestingly, these inhibitors can penetrate the blood-brain barrier, making their potential application possible in the treatment of central nervous system complications induced by COVID-19 (Valipour, 2023). The demonstrated biological properties of Tanshinone IIA also make it potentially useful in the treatment of various pathologies (Shang et al, 2012).…”
Section: S Miltiorrhiza Bunge (Dan Shen)mentioning
confidence: 99%
“…Tanshinone IIA was reported to be an inhibitor of MAPK p38 [450]. MAPK p38 is explored by many viruses for their efficient replications [47].…”
Section: Tanshinone Iiamentioning
confidence: 99%
“…MAPK p38 is explored by many viruses for their efficient replications [47]. Natural products that inhibit MAPK p38 activity might be a good candidate to exhibit broad-spectrum anti-viral activity [450], including DENV [43], coronavirus [44], VEEV [45], EV71 [46], SFTSV, HSV-1, and SARS-CoV-2 [47,450].…”
Section: Tanshinone Iiamentioning
confidence: 99%
See 1 more Smart Citation
“…However, it underscores the imperative for further preclinical trials to delineate p38 activation's role in SARS-CoV-2 animal models, emphasizing the necessity for comprehensive clinical trials to assess the efficacy and safety of p38 MAPK inhibitors in severe COVID-19 cases [ 40 ]. In the same context, Valipour [ 43 ] emphasized the potential of blood-brain barrier-penetrating p38 MAPK naturally occurring inhibitors in addressing CNS complications of COVID-19. This was highlighted through the characterization of tanshinone IIA and pinocembrin's therapeutic potential in treating these complications.…”
Section: Introductionmentioning
confidence: 99%